2017
DOI: 10.1177/0361684317701424
|View full text |Cite
|
Sign up to set email alerts
|

Raising Consciousness of Gender Roles Through Cross-Cultural Analysis

Abstract: Japan is in the midst of a major sociocultural shift in gender roles and, as a result, many women are choosing less traditional paths for their lives (Lachkar, 2014). However, traditional views of women's roles are slow to change (Yamamoto & Ran, 2014). Although more and more Japanese women are attending college to achieve their professional goals, many still express ambivalence about balancing career and marriage in their own lives (Anzai & Paik, 2012), and only a small percentage enter leadership positions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It was accordingly stated that differences might be the result of variation in willingness to report fantasies that are considered less acceptable by the society (Critelli and Bivona, 2008). Indeed, more recent research has found culture to play an important role in the expression of sexuality (Traeen et al, 2002), and this has become particularly evident when comparing European countries with, for instance, some Asian countries, in which sex differences in social roles, occupations, and expectations are amplified (Usui et al, 2003;Yamamoto and Ran, 2014;Smirles, 2017). The latter, indeed, show a general pattern of conservative attitudes about sexuality as well as limited knowledge about sexuality, regardless of biological sex (Okazaki, 2002;Nobre et al, 2003).…”
Section: Culture and Sexual Fantasiesmentioning
confidence: 99%
“…It was accordingly stated that differences might be the result of variation in willingness to report fantasies that are considered less acceptable by the society (Critelli and Bivona, 2008). Indeed, more recent research has found culture to play an important role in the expression of sexuality (Traeen et al, 2002), and this has become particularly evident when comparing European countries with, for instance, some Asian countries, in which sex differences in social roles, occupations, and expectations are amplified (Usui et al, 2003;Yamamoto and Ran, 2014;Smirles, 2017). The latter, indeed, show a general pattern of conservative attitudes about sexuality as well as limited knowledge about sexuality, regardless of biological sex (Okazaki, 2002;Nobre et al, 2003).…”
Section: Culture and Sexual Fantasiesmentioning
confidence: 99%
“…The significance of raising consciousness about the gender roles through cross-cultural analysis, especially given Japan's major sociocultural shift in gender roles, is also discussed in Smirles. This piece of research provides an insight into how the media and education could build perceptions and expectations towards female entrepreneurship, giving another cultural context an opportunity to apply similar strategies to also bring female entrepreneurs to the leading position [8].…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%